Qualitative Method Concepts: Literature Review, Focus Group Discussion, Ethnography and Grounded Theory - Candra Susanto, Primadi; Yuntina, Lily; Saribanon, Euis; Panatap Soehaditama, Josua; Liana, Esti (Siber Journal of Advanced Multidisciplinary, 2024)
Abstract: This study aims to build a hypothesis regarding the influence between variables that can later be used for further research within the scope of research methodology. Qualitative method articles: literature review, focus group discussion, ethnography, and grounded theory are scientific literature articles within the scope of research methodology. The approach used in this literature review research is descriptive qualitative. Data collection techniques use literature studies or review relevant previous articles. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and is sourced from academic online media such as the Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Emerald, Sage, WoS, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Literature review related to Qualitative Methods; 2) Focus Group Discussion related to Qualitative Methods; 3) Ethnography related to Qualitative Methods; and 4) Grounded Theory related to Qualitative Methods. Keywords: Qualitative Methods, Literature Review, Focus Group Discussion, Ethnography, Grounded Theory